Variation in Emergency Department Admission Rates Across the United States. (April 2013) - Pines, Jesse M.; Mutter, Ryan L.; Zocchi, Mark S.
There were more than 19 million hospitalizations in 2008 from hospital-based emergency departments (EDs), representing nearly 50% of all U.S. admissions. Factors related to variation in hospital-level ED admission rates are unknown. Generalized linear models were used to assess patient-, hospital-, and community-level factors associated with ED admission rates across a sample of U.S. hospitals using Healthcare Cost and Utilization Project data. In 1, 376 EDs, the mean ED admission rate, when defined as direct admissions and also transfers from one ED to another hospital, was 17.5% and varied from 9.8% to 25.8% at the 10th and 90th percentiles. Higher proportions of Medicare and uninsured patients, more inpatient beds, lower ED volumes, for-profit ownership, trauma center status, and higher hospital occupancy rates were associated with higher ED admission rates. Also, hospitals in counties with fewer primary care physicians per capita and higher county-level ED admission rates had higher ED admission rates.